Development of Postharvest Handling Technology for Tropical Tree Fruits : A workshop held in Bangkok, Thailand, 16-18 July 1992 - G.I. lohnson and E. Highley (Australian Centre for International Agricultura, 1994)

(untitled)
THIS workshop was an activity of AClAR Project No. 8844, 'The development of postharvest handling technology for selected tropical tree fruits'. The project was undertaken by collaborating research teams at the Queensland Department of Primary Industries in Australia, and the Department of Agriculture, the Thailand Institute of Scientific and Technological Research, and Chiang Mai and Kasetsart universities in Thailand. Cooperative research provided the opportunity to maximise benefits per research dollar expended, by reducing duplication of effort and providing additional 'fruit season' time within the life of a research program. Longer term benefits will accrue from the training and equipping of research scientists and facilities and from fostering government-to-government and researcher-to-researcher good will. Benefits and scientific breakthroughs can arise from the synergy of cooperative research sharing ideas, information, skills and pieces of the puzzle being solved